Iñupiatun Uqaluit Taniktun Sivuninit = Iñupiaq to English Dictionary - MacLean, Edna Ahgeak; MacLean, Edna Ahgeak (University of Alaska Press, 2014)
This is a comprehensive treatment of one of Alaska's oldest ancestral languages. Through its 19,000 entries and thirty-one appendices-with categories such as kin terms, names of constellations, and a list of explanations-the dictionary is an exceptional blend of linguistic and cultural references.